Building legal protection of land borders in the management of people-based economy - Bakung, Dolot Alhasni; Hadju, Zainal Abdul Aziz (Privietlab, 2026)
This study analyzes the legal protection of coastal boundary land within the framework of people-based economic management in Tomini Bay. Based on normative legal research methods, the study examined the 1945 Constitution Article 33, the 1960 Law, the Spatial Planning Law, Law 27/2007 jo. Law 1/2014, Presidential Regulation 51/2016 on coastal boundary boundaries, and Law 32/2009 on PPLH, to map the gap between norms and practices. The results of the analysis show three main problems: (1) weak implementation and enforcement of the law on violations of border utilization; (2) conflicts of control and ownership due to unclear land status, lack of mapping, and certification; and (3) unsustainable exploitation of resources that damages coastal ecosystems and threatens livelihoods. This study recommends strengthening legal certainty through participatory mapping and social certification, integrating national law with local wisdom (customary deliberation/mediation), and co-management models involving the government, community, and private sector. Thus, the Indonesian border land can be managed fairly, provide certainty of rights, and sustainably support coastal welfare.